2007
DOI: 10.1021/la063013k
|View full text |Cite
|
Sign up to set email alerts
|

Versatile and Efficient Synthesis of ω-Functionalized Asymmetric Disulfides via Sulfenyl Bromide Adducts

Abstract: Various types of asymmetric disulfides can be synthesized under mild conditions and in excellent yields by a method involving dialkoxylthiophosphoranesulfenyl halide precursors. This straightforward, rapid procedure is used to prepare a series of disulfides bearing neutral, acidic, and basic terminal groups as well as groups commonly used in biospecific self-assembled monolayers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…In this context, we report a regioselective sulfenylation at the C2 position of N -tosylindoles with sulfenylating reagents ( Scheme 1 E). Earlier studies demonstrated the application of readily available 5,5-dimethyl-2-thioxo-1,3,2-dioxaphosphorinane-2-disulfanyl derivatives for the preparation of functionalized unsymmetrical disulfides [ 60 , 61 , 62 , 63 , 64 ], α -sulfenylated carbonyl compounds [ 65 ], and unsymmetrical alkynyl sulfides [ 66 , 67 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, we report a regioselective sulfenylation at the C2 position of N -tosylindoles with sulfenylating reagents ( Scheme 1 E). Earlier studies demonstrated the application of readily available 5,5-dimethyl-2-thioxo-1,3,2-dioxaphosphorinane-2-disulfanyl derivatives for the preparation of functionalized unsymmetrical disulfides [ 60 , 61 , 62 , 63 , 64 ], α -sulfenylated carbonyl compounds [ 65 ], and unsymmetrical alkynyl sulfides [ 66 , 67 ].…”
Section: Introductionmentioning
confidence: 99%
“…To date, the most commonly utilized sulfenyl derivatives are sulfenyl chlorides, [4] S-alkyl thiosulfates and S-aryl thiosulfates (Bunte salts), [5] Salkylsulfanylisothioureas, [6] benzothiazol-2-yl disulfides, [7] benzotriazolyl sulfanes, [8] dithioperoxyesters, [9] (alkylsulfanyl)dialkylsulfonium salts, [10] 2-pyridyl disulfides and derivatives, [11] Nalkyltetrazolyl disulfides, [12] sulfonamides, [13] sulfenyldimesylamines, [14] sulfenyl thiocyanates, [15] 4nitroarenesulfenanilides, [16] thiolsulfinates and thiosulfonates, [17] sulfanylsulfinamidines, [18] thionitrites, [19] sulfenyl thiocarbonates, [20] thioimides, [21] and thiophosphonium salts. Earlier studies demonstrated the preparation of functionalized unsymmetrical molecules, such as dialkyl disulfides, [31] alkyl-aryl disulfides, [32] 'bioresistant' disulfides, [33] unsymmetrical disulfides of L-cysteine and L-cystine, [34] and diaryl disulfides [35] based on the readily available 5,5-dimethyl-2-thioxo-1,3,2-dioxaphosphorinane-2-disulfanyl derivatives. Recently, the oxidation of a mixture of two different thiols by 2,3-dichloro-5,6-dicyanobenzoquinone (DDQ) [29] or iridium (III) photoredox catalysis [30] to produce an unsymmetrical disulfide have also been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the oxidation of a mixture of two different thiols by 2,3-dichloro-5,6-dicyanobenzoquinone (DDQ) [29] or iridium (III) photoredox catalysis [30] to produce an unsymmetrical disulfide have also been reported. Earlier studies demonstrated the preparation of functionalized unsymmetrical molecules, such as dialkyl disulfides, [31] alkyl-aryl disulfides, [32] 'bioresistant' disulfides, [33] unsymmetrical disulfides of L-cysteine and L-cystine, [34] and diaryl disulfides [35] based on the readily available 5,5-dimethyl-2-thioxo-1,3,2-dioxaphosphorinane-2-disulfanyl derivatives. These disulfanyl derivatives of phosphorodithioic acid are convenient for the preparation of α-sulfenylated carbonyl compounds, [36] functionalized phosphorothioates, [37] and unsymmetrical alkynyl sulfides [38] as well as symmetrical [39] and unsymmetrical trisulfides.…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of unsymmetrical disulfides has been extensively investigated [15] whereby two general concepts have been employed. (i) Generation of an electrophilic sulfenyl derivative followed by reaction with a thiol or one of its derivatives [16][17][18][19][20][21][22][23][24] or (ii) oxidative heterocoupling. [25][26][27] The concept of an electrophilic reagent is appealing since it allows for a more controlled reactivity without the inherent distribution of products usually observed in oxidative heterocoupling, which relies on the electronic difference between the thiols.…”
Section: Introductionmentioning
confidence: 99%